Artificial Intelligence, Learning Evaluation, and Teacher Competence in Enhancing Social Studies Quality - Syamdani Syamdani; Elpisah Elpisah; Muhammad Fahreza W (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Amid rapid technological advancements, improving the quality of primary education remains a critical challenge. The purpose of this study is to determine the influence of Artificial Intelligence (AI), learning evaluation, and teacher competence on the quality of Social Studies instruction. The research used a quantitative design involving 25 sixth-grade students at SD Inpres Barua, Bontolempangan, during the 2024/2025 academic year through total sampling. Data were gathered via questionnaires and analyzed using multiple linear regression, t-tests, and F-tests in SPSS 26. Results revealed that AI, evaluation, and teacher competence significantly and positively affect learning quality both individually and collectively. These findings reinforce the critical role of digital tools and professional teaching standards in fostering more effective and meaningful learning experiences.